Dear land surveyors, veterans of the field and students, land surveyors! - Tretiak, А. (Land Management, Cadastre and Land Monitoring, 2018)
Professional holiday - Day of land surveyor - is celebrated in Ukraine every year from 2000 on the second Saturday in March. The date is established by Decree of the President of Ukraine No. 1556/99 of December 11, 1999 "On the day of land surveyor" in support of the initiative of the State Committee of Ukraine for Land Resources and the Union of Land Users of Ukraine and in the light of land reforms for the rational use and conservation of land resources.